2003
DOI: 10.1001/jama.289.14.1820
|View full text |Cite
|
Sign up to set email alerts
|

Zonisamide for Weight Loss in Obese Adults

Abstract: HE PREVALENCE OF OBESITY HAS increased dramatically in the past decade in the United States and many other developed countries. 1,2 Because obesity is associated with a significantly increased risk for type 2 diabetes, coronary heart disease, hypertension, numerous other major illnesses, and overall mortality from all causes, 3,4 weight reduction is critical for the obese patient. 5,6 There is good evidence that pharmacotherapy can enhance weight loss when combined with interventions aimed at changing lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
16

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(101 citation statements)
references
References 26 publications
2
83
0
16
Order By: Relevance
“…In some of the original studies with zonisamide (ZNS) for epilepsy, weight loss was a reported 'adverse event' (Tosches and Tisdell, 2006). Subsequently, in a randomized controlled trial, Gadde et al (2003) reported that ZNS caused significant weight loss among obese adults. McElroy et al (2006) have also suggested that ZNS might be an effective therapy for binge eating disorder.…”
Section: Introductionmentioning
confidence: 99%
“…In some of the original studies with zonisamide (ZNS) for epilepsy, weight loss was a reported 'adverse event' (Tosches and Tisdell, 2006). Subsequently, in a randomized controlled trial, Gadde et al (2003) reported that ZNS caused significant weight loss among obese adults. McElroy et al (2006) have also suggested that ZNS might be an effective therapy for binge eating disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss was an adverse effect associated with zonisamide treatment in clinical trials for epilepsy. Although the exact mechanism for this weight-reducing effect is unknown, the proposed mechanism includes alterated perception of taste due to carbonic anhydrase activity and modulation of dopamine and serotonin levels in the brain [241, 244, 245]. Empatic has shown promising results in phase 2 clinical trials [241] (Table 2 ).…”
Section: Combination Therapiesmentioning
confidence: 99%
“…O mecanismo de ação para a atividade anticonvulsivante da medicação não é totalmente esclarecido, mas acredita-se que esteja associado ao bloqueio de canais de sódio e cálcio. Evidências in vitro também demonstram que essa droga leva a aumento de atividade serotoninér-gica e dopaminérgica (30). Postula-se que esse mecanismo explique, pelo menos em parte, seus efeitos como agente redutor do peso.…”
Section: Bupropiona/zonisamidaunclassified